1999
DOI: 10.1143/jjap.38.1161
|View full text |Cite
|
Sign up to set email alerts
|

Schottky Characteristics of InAlAs Grown by Metal-Organic Chemical Vapor Deposition

Abstract: Schottky characteristics of InAlAs grown by metal-organic chemical vapor deposition (MOCVD) have been evaluated. InAlAs Schottky characteristics are strongly affected by MOCVD growth temperature. The reverse current of InAlAs grown at 700 • C is more than one order of magnitude larger than that at 750 • C. From deep-level transient spectroscopy (DLTS) measurements, electron traps with activation energies of 0.45, 0.33 and 0.15 eV have been observed in InAlAs grown at 700 • C.The results of C-V , Hall and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…During the past 20 years, there have been many reports and models on the formation of surface barrier and surface Fermi level pinning due to the existence of surface states. [1][2][3][4][5][6] In our previous reports, 7 we have investigated the energy band gap, the built-in electric fields, and the surface Fermi level positions of a series of In 1Ϫx Al x As surface intrinsic-n ϩ structures of different composition x and/or different undoped layer thickness at room temperature by photoreflectance. We found that over aluminum concentration of 0.42-0.57, the energy gap depends on the composition of the sample and the surface Fermi level is not pinned at midgap, as commonly believed, but instead varies, respectively, from 0.50 to 0.81Ϯ0.01 eV below the conduction band edge.…”
mentioning
confidence: 99%
“…During the past 20 years, there have been many reports and models on the formation of surface barrier and surface Fermi level pinning due to the existence of surface states. [1][2][3][4][5][6] In our previous reports, 7 we have investigated the energy band gap, the built-in electric fields, and the surface Fermi level positions of a series of In 1Ϫx Al x As surface intrinsic-n ϩ structures of different composition x and/or different undoped layer thickness at room temperature by photoreflectance. We found that over aluminum concentration of 0.42-0.57, the energy gap depends on the composition of the sample and the surface Fermi level is not pinned at midgap, as commonly believed, but instead varies, respectively, from 0.50 to 0.81Ϯ0.01 eV below the conduction band edge.…”
mentioning
confidence: 99%